(untitled) - Morita, Akio (New York, 1986)
Sony is one of the most powerful and respected multinational corporations in the world, and Akio Morita is its outspoken chairman. From his global perspective, Morita provides an informative and highly entertaining look at how Japanese business really works. TP: Plume.
Keywords: Electronic industries; History; Japan